The Problem of Developing Schoolchildren’s Cognitive Activities in the Educational Process - Benediktovna Tsarkova, Vera (2020)
This article aims to a research problem that emphasizes the necessity to guide and organize schoolchildren’s cognitive activities. In a situation when cognition becomes the leading activity, new opportunities are opened up for the organization of the whole educational process, including its other aspects such as – development, and learning. The experiment conducted revealed problem points of organizing the process of cognition as well as the necessity for collecting additional data for a future experiment. The paper also puts forward the idea of a correlation between the hierarchical system of principles of education and types of adequacy.